2023
DOI: 10.31004/joe.v5i4.2510
|View full text |Cite
|
Sign up to set email alerts
|

Analyse the Role of Family in Entrepreneurship Education: Effective Support and Assistance

Abstract: Entrepreneurship education is considered important in developing entrepreneurial skills and preparing individuals to start their own business. One of the factors that influence an individual's ability to start a business is the family's role in supporting entrepreneurship education. This research aims to discuss the role of family in supporting entrepreneurship education and provide useful information for individuals, families, and educational institutions in improving entrepreneurship education. This research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…’s (2021) empirical findings demonstrate that, through the mediating effect of self-efficacy and risk propensity, social networking sites make a positive and substantial contribution to GE intentions. As claimed by Raharjo et al. (2023), there is empirical evidence of the connection between entrepreneurship education and GESE .…”
Section: Development Of Hypothesesmentioning
confidence: 89%
“…’s (2021) empirical findings demonstrate that, through the mediating effect of self-efficacy and risk propensity, social networking sites make a positive and substantial contribution to GE intentions. As claimed by Raharjo et al. (2023), there is empirical evidence of the connection between entrepreneurship education and GESE .…”
Section: Development Of Hypothesesmentioning
confidence: 89%
“…Through education, individuals are given the opportunity to broaden their horizons, hone the skills necessary for success in life, and internalise the values that Vol.1, No.1, February 2024, DOI : https://doi.org/10.61100/tender.v1i1.146, pages. 7-13 shape their character (Cahyono et al, 2023;Raharjo et al, 2023). More than just the channelling of information, education is also the foundation that enables one to actively participate in society, contribute to social and economic development, and adapt to ongoing changes in an increasingly complex global environment Rukman et al, 2023).…”
Section: Literature Review Educationmentioning
confidence: 99%
“…According to research [34], aspiring entrepreneurs are more likely to seek for, evaluate, and act upon novel opportunities when they have access to appropriate planning, organization, process, and material resources. Previous studies have shown a correlation between aspiring entrepreneurs and actual business owners [35] [36] [37] [38]. The term "entrepreneurial attitude" describes a person's dedication to starting and running their own business [39].…”
Section: Entrepreneurial Mindset and Students' Entrepreneurial Intentionmentioning
confidence: 99%